2018
DOI: 10.1016/j.jconrel.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based pharmacokinetic (MBPK) models describe the complex plasma kinetics of three antiretrovirals delivered by a long-acting anti-HIV drug combination nanoparticle formulation

Abstract: Existing oral antiretroviral (ARV) agents have been shown in human studies to exhibit limited lymph node penetration and lymphatic drug insufficiency. As lymph nodes are a reservoir of HIV, it is critical to deliver and sustain effective levels of ARV combinations in these tissues. To overcome lymph node drug insufficiency of oral combination ARV therapy (cART), we developed and reported a long-acting and lymphocyte-targeting injectable that contains three ARVs-hydrophobic lopinavir (LPV) and ritonavir (RTV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 55 publications
4
39
0
1
Order By: Relevance
“…This combination was dubbed "the targeted, long-acting and combination anti-retroviral therapy" (TLC-ART). The main findings were enhanced and showed persistent drug levels throughout the body of NHPs for over a week [114], and importantly not exclusively in the draining, sentinel lymph nodes [110,112,116]. However, more research is needed in order to fully understand how compounds are retained intra-lymphatically.…”
Section: Increasing Access Of Drugs To Lymphoid Tissuesmentioning
confidence: 99%
“…This combination was dubbed "the targeted, long-acting and combination anti-retroviral therapy" (TLC-ART). The main findings were enhanced and showed persistent drug levels throughout the body of NHPs for over a week [114], and importantly not exclusively in the draining, sentinel lymph nodes [110,112,116]. However, more research is needed in order to fully understand how compounds are retained intra-lymphatically.…”
Section: Increasing Access Of Drugs To Lymphoid Tissuesmentioning
confidence: 99%
“…While the exact physiological mechanisms leading to targeted delivery of drug combinations in cells for an extended time remains to be elucidated in detail, we found that DcNPs are first taken up into lymph vessels from the subucutaneous space, and subsequently undergo lymphatic first-pass distribution and retention throughout the channels of lymph vessel and node network in the body; this retention of drug in lymph vessels and nodes throughout the body is key to the lymphocyte-targeting and long-acting properties of DcNPs. More detailed discussions of a working hypothesis can be found in these recent papers [61,137,138]. Reviews by our group describe some important results obtained with lipid nanoparticles for drug delivery to lymph nodes and have further discussion on relevant targeting mechanisms [139][140][141].…”
Section: Lymph Nodesmentioning
confidence: 99%
“…Free CAB or RPV released into the extracellular fluid from the intramuscular depot is taken up immediately into the rapidlyflowing blood capillaries, bypassing an opportunity to instead be taken up predominantly by lymphatic capillaries from the intramuscular space, distribute through the lymphatics and accumulate in lymph nodes to produce long-acting PK in both the plasma and lymphocytes. This dissolution and absorption behavior of CAB LA and RPV LA is in contrast to drug combination nanoparticle-associated antiretrovirals in TLC-ART101 that cleared readily form the SC injection site, were predominantly taken into lymph capillaries instead of the blood, distributed through lymph vessels to lymph nodes throughout the body, reached peak plasma levels in non-human primates at ~6 to ~8 hours after injection, and had higher drug levels in lymph node and peripheral blood mononuclear cells than in the plasma [61,137,138]. A recent MRI study of CAB LA in rats confirmed that both intramuscular and SC depots did not readily clear from the injection site and did not distribute to and accumulate in multiple lymph nodes throughout the rat; moreover, consistent with human data, peak plasma drug levels of these drugs after both routes of injection were only achieved after multiple days and had similar shapes in their plasma absorption curves, indicating similar pathways of absorption (from the injection site directly to the blood) but slightly different rates and extents of absorption (likely due to physiological and dissolution rate differences between the two injection sites) [149].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peneliti berpendapat bahwa hal tersebut dapat terjadi karena adanya fakto -faktor yang lain yang lebih dominan yang menyebabkan responden tidak serius dalam menjalani pengobatan. Jika dilihat dari faktor demografi faktor -faktor tersebut adalah usia responden, lamanya menderita penyakit, serta jarak yang harus ditempuh oleh responden dari rumah untuk mengambil obat ARV (Kraft et al, 2018).…”
Section: Perceived Severityunclassified